Shaping Critical Thinking: Teachers' Perspectives on Digital Literacy and Innovation - Aghnia Adawiyyah Muslih, Raden; Perda, Meri (Journal of English Education and Teacher Trainer, 2025)
This study explores the relationship between critical thinking and digital literacy from teachers' perspective. As education increasingly embraces digital tools, teachers play a pivotal role in fostering critical thinking skills through innovative digital literacy practices. This paper presents a literature review highlighting how digital literacy can promote critical thinking. Furthermore, the study analyzes teachers' perspectives and challenges in using digital literacy to enhance students' critical thinking. It also provides recommendations for best practices, emphasizing the need for ongoing professional development and collaborative efforts among teachers. The findings underscore the importance of empowering teachers with the necessary skills and resources to create a classroom environment that embraces digital tools and nurtures students' critical thinking abilities, preparing them for the demands of the digital age.